Application of the Environmental Exploration Approach (JAS) Assisted by QR Codes to Increase Scientific Literacy Aspects of Competency and Conservation Attitudes in Plantae Material - Darwati, Een; Ubaidillah, Mujib; Sahrir, Dede Cahyati; Oktina Sari, Annisa Oktina Sari (Biosfer: Jurnal Tadris Biologi, 2023)
The purpose of this study was to describe student learning activities, to analyze the differences in increasing scientific literacy in the aspect of student competency and to analyze the increase in conservation attitudes of class X students in plantae material which was taught using the Natural Surroundings (JAS) approach assisted by the QR Code. This research is a quantitative study with a sample of 31 students of class X MIPA 1 control class and 32 students of class X MIPA 3 experimental class. The research design used was the pretest posttest control group model. Data collection techniques in this study used observation, tests and questionnaires. The results showed that there was an increase in student learning activities at each meeting. There is a significant difference in increasing scientific literacy in the competency aspect in indicator 2 with a significance value of 0.000. And there is an increase in conservation attitudes after the learning treatment. Based on the results of the study it can be concluded that the application of learning using the Natural Surrounding Exploration (JAS) approach assisted by the QR Code can increase student learning activities, scientific literacy aspects of competence and students' conservation attitudes towards biology learning.ABSTRAK: Tujuan dalam penelitian ini yaitu untuk mendeskripsikan aktivitas belajar siswa, untuk menganalisis perbedaan peningkatan literasi sains aspek kompetensi siswa dan untuk menganalisis peningkatan sikap konservasi siswa kelas X pada materi plantae yang diajarkan dengan pendekatan Jelajah Alam Sekitar (JAS) berbantuan QR Code. Penelitian ini merupakan penelitian kuantitatif dengan sampel sebanyak 31 siswa kelas X MIPA 1 kelas kontrol dan 32 siswa kelas X MIPA 3 kelas eksperimen. Desain penelitian yang digunakan yaitu model pretest posttest control group. Teknik pengumpulan data dalam penelitian ini menggunakan observasi, tes dan angket. Hasil penelitian menunjukkan bahwa terdapat peningkatan aktivitas belajar siswa pada setiap pertemuan. Terdapat perbedaan peningkatan literasi sains aspek kompetensi yang signifikan pada indikator 2 dengan nilai signifikansi 0,000. Dan terdapat peningkatan sikap konservasi setelah perlakuan pembelajaran. Berdasarkan hasil penelitian dapat disimpulkan bahwa penerapan pembelajaran dengan menggunakan pendekatan Jelajah Alam Sekitar (JAS) berbantuan QR Code dapat meningkatkan aktivitas belajar siswa, literasi sains aspek kompetensi dan sikap konservasi siswa terhadap pembelajaran biologi.